2013
DOI: 10.1007/s11051-013-1846-4
|View full text |Cite
|
Sign up to set email alerts
|

Probing the structure of Fe nanoparticles in multiwall carbon nanotubes grown on a stainless steel substrate

Abstract: International audienceWe investigated the local order in individual iron nanoparticles (NPs) embedded in carbon nanotubes (CNTs). The NPs directly come from the CNT growth on stainless steel without addition of external metal catalyst. The structural analysis has been obtained through nanoscale transmission extended electron energy loss fine structure (EXELFS) measurements above the iron L2,3 edge. A theoretical simulation of the EXELFS features has been performed within the multiple scattering theory. By comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Moreover, MWCNTs come with a wide distribution of tube diameters, with average value 58.19 ± 18.35 nm. Also, we have shown in our past works [43][44][45][46] transmission electron microscopy (TEM) images confirming the multi-walled nature of the as-grown carbon nanotubes. Furthermore, in figures 1(b), (d) it may be observed that MWCNTs are mostly capped and often they present carbonaceous nanostructures (amorphous and/or graphitic carbon) around the tips (figure 1(d)) and close to the stainless steel surface (figure 1(c)), with a characteristic dimension of 100 nanometers, as also reported by other authors [42].…”
Section: Microscopic Characterization Of Mwcnt Filmssupporting
confidence: 71%
See 1 more Smart Citation
“…Moreover, MWCNTs come with a wide distribution of tube diameters, with average value 58.19 ± 18.35 nm. Also, we have shown in our past works [43][44][45][46] transmission electron microscopy (TEM) images confirming the multi-walled nature of the as-grown carbon nanotubes. Furthermore, in figures 1(b), (d) it may be observed that MWCNTs are mostly capped and often they present carbonaceous nanostructures (amorphous and/or graphitic carbon) around the tips (figure 1(d)) and close to the stainless steel surface (figure 1(c)), with a characteristic dimension of 100 nanometers, as also reported by other authors [42].…”
Section: Microscopic Characterization Of Mwcnt Filmssupporting
confidence: 71%
“…Recently, we have shown [43][44][45][46] that the direct growth of high quality MWCNTs on stainless steel in the absence of any external catalysts is possible. Moreover, acid treatments and oxidation-reduction stages on this type of surface are not necessary because of the native nano-scale roughness of the substrate and the iron-rich substrate surface both act as an efficient catalyst or template in the synthesis of MWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…The possible View Article Online conversion of Fe during thermal treatments or the synthesis of CNTs is documented in some papers. 45,[50][51][52] In Fig. 1c and in the corresponding inset, the 2q z 24.6 -25.6 feature, due to the formation of the TiO 2 phase (anatase), is also observed.…”
Section: Morphology and Structure Of The Tio 2 /Mwcnts Graed On Stainless Steelmentioning
confidence: 75%
“…From this standpoint, stainless steel, as an economic material with a high content of iron as the catalyst for CNT synthesis, is an interesting candidate. In fact, several groups have conducted research on direct growth of CNT on stainless steel [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Generally, the interest behind this area of research is multiple, including electrodes for supercapacitors [24][25][26], sensor technology [27][28][29][30], fuel cells [31,32], batteries [33], catalyst support for wastewater treatment [10], field emission probes [34][35][36][37][38] and low friction applications [39][40][41].…”
Section: Introductionmentioning
confidence: 99%